Corrosion Barrier Coatings: Progress and Perspectives of the Chemical Route - George Kordas (Corrosion and Materials Degradation, 2022)
Improved corrosion barrier coatings (CBCs) to protect metals will allow future metal structures to operate for extended periods, ensuring improved safety by reducing environmental pollution and maintenance costs. Many production methods and design of corrosion barrier coatings (CBCs) have been developed. This review focuses only on CBCs made with chemistry techniques. These CBCs can be passive and active with remarkable performance. Today, most of the work focuses on the discovery and application of “smart nanomaterials,” which, if incorporated into “passive CBCs,” will turn them into “active CBCs,” giving them the phenomenon of “self-healing” that extends their service life. Today, many efforts are focused on developing sensors to diagnose corrosion at an early stage and CBCs that self-diagnose the environment and respond on demand. In addition, recent technological developments are reviewed, and a comprehensive strategy is proposed for the faster development of new CBC materials.